2017
DOI: 10.15237/gida.gd17019
|View full text |Cite
|
Sign up to set email alerts
|

Ni̇ğde Yöresi̇nde Tüketi̇me Sunulan Peyni̇rlerde Akar Varliğinin Araştirilmasi

Abstract: ÖzBu çal›flma, Ni¤de peynirlerinde akar varl›¤›n›n ortaya ç›kar›lmas› ve bölgenin akar enfestasyonu durumunun saptanmas› amac›yla yap›lm›flt›r. Bu amaçla, Haziran-Kas›m 2011 tarihleri aras›nda Ni¤de'den toplam 226 adet peynir (61 adet kaflar ve 165 adet tulum) toplanm›fl ve akar varl›¤› yönünden incelenmifltir. Çal›flma sonucunda incelenen 226 adet peynir numunesinin 2 (%0.88)'sinde Acarus siro varl›¤› tespit edilmifltir. Akarlar›n peynirlerdeki ayl›k prevalans› %0-2 aras›nda belirlenmifltir. Aylara göre A. si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…33 In 1943, Brucella was first diagnosed in animals and humans by serological methods in Türkiye by Dr Golem. [34][35][36] Dr Golem examined the Brucella cases reported to the Ministry of Health between 1930 and 1948 in his article titled "The Situation of Brucellosis in Our Country" (1949) and found that 10% of the cases occurred in the first four months of the year, 56% in the second four months of the year, and 34% in the last four months of the year. He said that since almost half of Türkiye's population was engaged in farming then, it was more common among people living a rural way of life.…”
Section: Dr Golem's Studies In Türkiyementioning
confidence: 99%
“…33 In 1943, Brucella was first diagnosed in animals and humans by serological methods in Türkiye by Dr Golem. [34][35][36] Dr Golem examined the Brucella cases reported to the Ministry of Health between 1930 and 1948 in his article titled "The Situation of Brucellosis in Our Country" (1949) and found that 10% of the cases occurred in the first four months of the year, 56% in the second four months of the year, and 34% in the last four months of the year. He said that since almost half of Türkiye's population was engaged in farming then, it was more common among people living a rural way of life.…”
Section: Dr Golem's Studies In Türkiyementioning
confidence: 99%